1997
DOI: 10.1046/j.1365-2141.1997.4673271.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AML1/MTG8 transcripts in clonogenic cells grown from bone marrow of patients in remission of acute myeloid leukaemia with t(8;21)

Abstract: Summary.Patients in long-term remission of acute myeloid leukaemia (AML) M2 with t(8;21) after chemotherapy, with or without bone marrow transplantation, are known to retain residual cells which express AML1/MTG8 transcripts in bone marrow, detectable by RT-PCR. In order to determine whether these residual cells are clonogenic, we have grown remission bone marrow samples in standard semi-solid culture and picked individual CFU-GM and BFU-E colonies which were then analysed for the expression of AML1/MTG8 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…18 Thus, preleukemic stem cells and LSCs may coexist and vary in their differentiative and proliferative properties and perhaps their response to therapy, that is, persistence of preleukemic stem cells but eradication of fully transformed LSCs. This could explain why AML1-ETO transcripts remain detectable in the blood and, at a low frequency, in various clonogenic progenitors in many patients with AML1-ETO AML in long-term remission, [55][56][57][58] whereas a second mutation (eg, KIT) becomes undetectable despite similar detection sensitivities. 67 The persistence of preleukemic stem cells is similarly supported by X chromosome inactivation studies showing persistently clonal hematopoiesis in some patients in morphologic remission after treatment for AML.…”
Section: Leukemic and Preleukemic Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Thus, preleukemic stem cells and LSCs may coexist and vary in their differentiative and proliferative properties and perhaps their response to therapy, that is, persistence of preleukemic stem cells but eradication of fully transformed LSCs. This could explain why AML1-ETO transcripts remain detectable in the blood and, at a low frequency, in various clonogenic progenitors in many patients with AML1-ETO AML in long-term remission, [55][56][57][58] whereas a second mutation (eg, KIT) becomes undetectable despite similar detection sensitivities. 67 The persistence of preleukemic stem cells is similarly supported by X chromosome inactivation studies showing persistently clonal hematopoiesis in some patients in morphologic remission after treatment for AML.…”
Section: Leukemic and Preleukemic Stem Cellsmentioning
confidence: 99%
“…Also consistent with the notion of a founder mutation, or at least a very early event, is the demonstration of AML1-ETO in other patients in long-term remission after therapy for CBF AML. [55][56][57][58] Furthermore, the observation that aberrant CEBPA, DNMT3A, IDH1/2, and possibly NPM1 alleles are typically present at diagnosis and relapse suggests that these could be very early, possibly preleukemic, mutational events. [59][60][61][62] In contrast, the mutation status of FLT3, NRAS/KRAS, and WT1 often changes between diagnosis and relapse, and mutations may only be present in a subset of leukemic blasts, indicating a role as secondary events.…”
Section: Leukemic and Preleukemic Stem Cellsmentioning
confidence: 99%
“…Several studies have demonstrated persistent expression of the AML1-ETO chimaeric mRNA in patients in long-term remission, including those treated with allogeneic bone marrow transplantation (Nucifora et al, 1993d;Guerrasio et al, 1995;Saunders et al, 1996;Jurlander et al, 1996;Miyamoto et al, 1996). In addition, persistent expression of AML1-ETO was detected in the clonogenic haemopoietic progenitors isolated from remission bone marrow samples obtained from patients who had been in remission off therapy for several years (Miyamoto et al, 1996;Saunders et al, 1997). Importantly, AML1-ETO expression was detected not only in myeloid/monocytic colonies, but also in erythroid colonies, suggesting that despite being in remission the bone marrow of these patients had retained viable multipotential haemopoietic progenitors containing t(8;21).…”
Section: Figmentioning
confidence: 99%
“…(3) AML1-ETO can be detected in the peripheral blood and marrow of patients with long-term complete remissions after treatment with chemotherapy or stem cell transplantation (Kusec et al, 1994;Miyamoto et al, 1995;Nucifora et al, 1993b;Saunders et al, 1994Saunders et al, , 1996. AML1-ETO positive, multipotent progenitor cells that yield normal blood cell colonies, including B cells can be demonstrated in these patients along with normal progenitors (Guerrasio et al, 1995;Miyamoto et al, 1996Miyamoto et al, , 2000Saunders et al, 1997). This strongly suggests that the AML1-ETO fusion event occurs in an early stem cell or progenitor cell and that additional events are required for the cell to become fully transformed.…”
Section: T(8;21) and The Disruption Of Aml In Leukemiamentioning
confidence: 99%